Identification of key genes affecting ventilator-induced diaphragmatic dysfunction in diabetic mice - Xing, Rongchun; Yu, Haibo; Yu, Jiangtao; Zeng, Rong; Xiang, Zhijun; Ma, Haoli; Li, Gang; Zhao, Yan (Frontiers in Genetics, 2024)
Mechanical ventilation (MV) can maintain alveolar ventilation, increase lung volume, maintain oxygenation, and reduce respiratory work, which is a life-saving measure. However, long-term mechanical ventilation can lead to ventilator-induced diaphragmatic dysfunction (VIDD), which is manifested as diaphragmatic atrophy, decreased contractile force and progressive aggravation, and difficulty in exiting ventilator, which is closely related to poor clinical prognosis. Diabetes is one of the most common metabolic diseases, with a high incidence worldwide, and the prevalence of type 2 diabetes is increasing alarmingly worldwide, with explosive increases in low-income countries and among adolescents/young adults, and with serious implications for longevity and quality of life. The diagnosis, prevention and treatment of the disease face great challenges. Clinically, some critically ill patients often need mechanical ventilation. If these critically ill patients have diabetes combined with mechanical ventilation, the prognosis is generally poor, and many studies have shown that diabetes can cause diaphragmatic dysfunction. Existing studies on the mechanisms of diabetes-induced muscle damage mostly focus on mitochondrial oxidative stress. Diabetes may be an important factor in aggravating VIDD. However, previous studies on VIDD models were mostly based on wild-type healthy mouse or rat MV models, and the current omics studies were mostly focused on rat models. So far, there has been no study on transcriptomic analysis of diaphragm in MV model of diabetic mice. In order to understand the changes in mRNA levels caused by mechanical ventilation in patients with diabetes, we used a unique experimental ICU model. Firstly, BKS-DB (DB) mice were selected as the diabetes model (BKS-DB mice were severely obese with significant and continuous glucose increase after Lepr gene was knocked out on C57BL/6JGpt mice. Islet atrophy, which may be accompanied by diabetic nephropathy, diabetic retinopathy, and other symptoms). Then, BKS-DB diabetic mice were given mechanical ventilation for 12 hours and diaphragm mRNA expression levels were detected by high-throughput sequencing, compared with C57BL/6J (C57) control mice. Finally, we verified the expression of the selected mRNAs using qRT-PCR.